2009
DOI: 10.1038/ja.2009.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cobalt and vitamin B12 on the production of salinosporamides by Salinispora tropica

Abstract: NPI-0052 ( Figure 1) is a novel, potent proteasome inhibitor 1,2 isolated from a marine actinomycete Salinispora tropica. 3 It possesses a broad spectrum of activities against various tumors in animal models, 1,2,4,5 and is currently being evaluated in clinical trials for the treatment of patients with hematologic and solid tumor malignancies. 2 A saline fermentation process for the large scale production of NPI-0052 has been developed to supply NPI-0052 for clinical study. Owing to the structure similarity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…The initial cultivation conditions of S. tropica to obtain 4 [27] had to be adjusted to allow the manufacture of larger quantities in sufficient quality for application to humans. The optimization of production titers was explored in a variety of studies,[112,123126] which led: 1) to the establishment of a fermentation protocol based on an XAD (hydrophobic cross-linked polystyrene copolymer absorbent) resin[127] which helps to overcome the loss of yield caused by the instability of 4 in aqueous media,[128] 2) the discovery of more efficient producing organisms by strain screening and selection, and 3) the development of the first industrial-scale saline fermentation process to meet current Good Manufacturing Practice (cGMP) guidelines. Taken together, these efforts towards the enhanced production of 4 led to an approximately 100-fold increase in isolated 4 , thus rendering the process suitable for the biotechnological production on an industrial scale and clinical evaluation of 4 .…”
Section: Salinosporamide a In Cancer Therapymentioning
confidence: 99%
“…The initial cultivation conditions of S. tropica to obtain 4 [27] had to be adjusted to allow the manufacture of larger quantities in sufficient quality for application to humans. The optimization of production titers was explored in a variety of studies,[112,123126] which led: 1) to the establishment of a fermentation protocol based on an XAD (hydrophobic cross-linked polystyrene copolymer absorbent) resin[127] which helps to overcome the loss of yield caused by the instability of 4 in aqueous media,[128] 2) the discovery of more efficient producing organisms by strain screening and selection, and 3) the development of the first industrial-scale saline fermentation process to meet current Good Manufacturing Practice (cGMP) guidelines. Taken together, these efforts towards the enhanced production of 4 led to an approximately 100-fold increase in isolated 4 , thus rendering the process suitable for the biotechnological production on an industrial scale and clinical evaluation of 4 .…”
Section: Salinosporamide a In Cancer Therapymentioning
confidence: 99%
“…Die ursprünglichen Kulturbedingungen von S. tropica zur Gewinnung von 4 27 mussten jedoch angepasst werden, um die Produktion größerer Mengen in ausreichender Qualität zur Anwendung am Menschen zu ermöglichen. Die Optimierung der Produktionstiter wurde in einer Vielzahl von Studien untersucht,112, 123126 und aus diesen resultierten 1) die Etablierung einer XAD‐Harz‐basierten (XAD=ein hydrophobes, vernetztes, Polystyrol‐Copolymer‐Adorbens) Fermentationsvorschrift,127 die hilft, Ausbeuteverluste aufgrund der Instabilität von 4 in wässrigen Medien128 zu verhindern, 2) die Entdeckung effizienterer Produzentenorganismen durch Stamm‐Screening und ‐Selektion sowie 3) die Entwicklung des ersten im Industriemaßstab durchgeführten salinen Fermentationsprozesses nach den “Current Good Manufacturing Practice”(cGMP)‐Richtlinien. Zusammengenommen ergaben diese Versuche zur verstärkten Produktion von 4 einen ungefähr 100‐fachen Zuwachs an isoliertem 4 und stellten damit einen Prozess zur Verfügung, der zur biotechnologischen Produktion im Industriemaßstab und zur klinischen Evaluierung von 4 geeignet ist 26.…”
Section: Salinosporamid a In Der Krebstheraphieunclassified
“…The production of 5 in the control culture and the butyrate-fed culture were significantly less than reported in our previous publication [55] because the NaCl-based medium used in this study contains cobalt chloride. We have demonstrated that cobalt and vitamin B 12 inhibit the production of 5 [58]. Even though the absolute amounts of production of 5 in these two studies are different, the effect of butyrate in increasing the production of 5 is the same (4.3-fold versus 4.2-fold).…”
Section: Natural and Unnatural Products Of S Tropicamentioning
confidence: 99%
“…Fermentation Optimization of 1 to Clinical Trials Materials). In parallel, S. tropica was further exploited in several important ways: (i) structurally related natural products were identified [5153] (see Section 2.1 Natural Products of S. tropica); (ii) modified media and precursor-directed biosynthesis gave rise to new chemical entities, altered the ratios of secondary metabolites, and offered insights into the biosynthetic pathways of 1 and analogs [52,5458] (see Section 2.3 Products of Precursor-Directed Biosynthesis); (iii) access to large quantities of 1 through fermentation enhanced its utility as a precursor for semi-synthesis [34,52,59–61] (see Section 4. Products of Semi-Synthesis); (iv) its genome was sequenced [62]; and (v) knockout mutants were generated, opening the door to bioengineered products [6366] (see Section 2.4 Products of Mutasynthesis).…”
Section: Introductionmentioning
confidence: 99%